Türkiye'de bölücü terör örneği PKK ve gençlik örgütlenmesi - Akkurt, Mutlu (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2010)
Türkiye'de birçok terör örgütü halen faaliyetlerine devam etmektedir. Özellikle bölücü terör örgütü olan PKK eylemleriyle ülke gündemini meşgul etmekte, devamlı değişen gençlik yapılanmalarıyla genç yaş grubundan örgüte eleman kazandırmayı amaçlamaktadır. Kaynak Taraması tekniğiyle yazılan bu tezde PKK terör örgütünün kuruluş ve gelişimi, tarihsel süreç içinde incelenmiş; gençlik yapılanmaları ise, mevcut kaynak ve belgelerin sınırlılığı nedeniyle belli ölçüde verilebilmiştir.Üç bölümden oluşan çalışmanın ilk bölümünde, terörizmin tanımı ve tarihi kökeni ile Türkiye'de faaliyet gösteren terör örgütleri hakkında genel bilgiler verilmiştir. İkinci bölümde, PKK örgütü çeşitli yönleriyle ele alınmıştır. Üçüncü bölümde PKK örgütünün 1987 yılından günümüze kadarki gençlik örgütlenmeleri irdelenmiştir. Sonuç kısmında ise, genel bir değerlendirme ve politika önerileri sunulmuştur.

Several terrorist organizations continue their activities in Turkey today. Particularly the PKK (the Kurdistan Workers? Party), which is known as a separatist terrorist organization, occupies the agenda of Turkey with its actions, and aims at gaining members amongst the youngsters through continuously changing youth branches. In this thesis, the establishment and development of the PKK is examined in historical process by the method of literature review; and its youth branches are limitedly explored because of limited sources and documents.The thesis constitutes three main parts. The first part gives information in general about the definition of terrorism, its historical background, and terrorist organizations which have been active in Turkey. The second part examines the PKK organization from its various aspects. The third part addresses the youth branches of the PKK organization, which are active since 1987. A general evaluation and some policy suggestions are given as the conclusion.
The PKK as an example of separatist terror organization in Turkey and its youth organizing
Keywords: Kamu Yönetimi; Public Administration